ODBFT: An Optimal Derivative based Byzantine Fault Tolerance of Blockchain Consensus Algorithm with Smart Digital Contract for Health Monitoring System - Devi, V. Sarala; Rammohan, S. Radha; K., Sheela; Vaidehi, V.; Jayashri, N. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Blockchain technology starts with crypto currency called Bitcoin. Followed by Smart contract is called digital contract, which is defined as pieces of decentralized code. It performs self-sufficient operation are executed automatically to meet certain conditions. Compared with Bitcoin application, Blockchain technology is more powerful. Overall opportunity of Blockchain technology is increasing and applicable in industry, financial transaction and healthcare system. Consensus is a digital agreement or procedure to make a common decision or agreement in a decentralized network. Different methods of consensus are used in Blockchain environment and Bitcoin network. In decentralized environment, multiple nodes can take own decision whereas some nodes act as a malicious node or faulty node. Blockchain and the Internet of Things (IoT) are fast-growing technologies this can be easily integrated and applied in various services, especially for Health Monitoring System (HMS) applications. In smart HMS, IoT devices have the functionality to store, process, and analyze sensed data collected from end user data. Storage of data is also challenging because it must consider legitimate elements, a single point of failure, data manipulation, tampering, and security. To mitigate such problems, integrate Blockchain technology and store of patient sensed data for decentralized computation. In this research, concentrate on consensus mechanism and cognitive smart digital contract in Blockchain network. Propose a decentralized Cognitive Blockchain-based HMS (CBC-HMS). Cognitive blockchain framework is combination of Cognitive Consensus Algorithm with Design a Optimal Derivative based Byzantine Fault Tolerance (ODBFT) consensus technique for a blockchain with IoT technology.Through this research work, two Byzantine Fault Tolerance (BFT) consensus algorithms are proposed for improving the consensus process, reduces fault and improve the lifetime of the network with energy efficiency. Detailed review of PBFT, Paxos, RAFT, PoA, PoAh consensus algorithms is discussed. Also to improve the decision making skill for blockchain introduced cognitive smart digital contract which creates high potential action aggrement. Proposed ODBFT algorithm compared the faulty rate, security, scalability and throughput of consensus mechanism with existing models. Finally, the advantages and disadvantages of the consensus algorithms are compared.The results show that proposed ODBFT solves the problem of Byzantine faults and guarantees stable performance.